Canine Mammary Mixed Tumours: A Review. (21st October 2012) - Dantas Cassali, Geovanni; Cavalheiro Bertagnolli, Angélica; Ferreira, Enio; Araújo Damasceno, Karine; de Oliveira Gamba, Conrado; Bonolo de Campos, Cecília
Abstract : Mammary mixed tumours are the most frequent neoplasias in female dogs. In humans, mixed tumours are frequently found in the salivary glands and are known as pleomorphic adenomas. In addition to their histomorphologic similarities, mixed tumours and pleomorphic adenomas have the potential to become malignant and give rise to carcinomas in mixed tumours and carcinomas ex-pleomorphic adenoma, respectively. The factors associated with malignant transformation are still poorly known in the case of canine mixed tumours. However, this form of neoplasia tends to be associated with a better prognosis than other malignant histological types. This paper discusses the main features associated with female canine mammary mixed tumours.